HYPNOBREASTFEEDING, STARTING EXCLUSIVE BREASTFEEDING TO BE SUCCESS - ni wayan armini (Poltekkes Kemenkes Denpasar, 2016)
Abstract: Mother's Milk is the best food for infants, but often a bottleneck in exclusive breastfeeding. Various factors contributed to the failure of exclusive breastfeeding, one of which is the production of milk slightly. Hypnobreastfeeding help mothers to ensure that breastfeeding mothers can continue breastfeeding, minimal exclusively during the first six months, especially if the breast-feeding mothers must return to work.. Hypnobreastfeeding are relaxation techniques to help smooth the process of breastfeeding . The trick insert sentences positive affirmations that help breastfeeding when mothers are relaxed or very concentrated on one thing. This article aims to provide an overview of hypnobreastfeeding can provide solutions to augment milk production in breastfeeding and overcome obstacles . Expected every mother is able to provide exclusive breastfeeding to their babies without significant barriers. Keywords: Exlusive breastfeeding, hypnobreastfeeding, affirmation, relaxation